Influence of gender role on internet usage pattern at home among academicians - Komathi, Munusamy; Ismail, Maimunah (The Journal of International Social Research, 2009)

(untitled)
The paper examines gender differences in Internet usage pattern among male and female academicians. Internet usage pattern covers items such as knowledge and experience on the Internet, purpose of using Internet and frequency of using e-mail. The paper also examines the influence of gender role on Internet usage pattern. The data of this qualitative study were based on interviews with five academicians in a private university in Malaysia. The study shows that gender role to certain extent does influence Internet usage pattern at home. Women are seen to have more limitations compared to men to access to the Internet at any time due to family commitment.